2018
DOI: 10.1016/j.toxrep.2018.08.019
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of concentration and toxicological (Cancer) risk of lead, cadmium and chromium in tobacco products commonly available in Bangladesh

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The HI values for adults and children ascended as follows: As > Cr > V > Pb > Ni > Cu > Cd > Zn ( Figure 4 A,B). An HI value of ˂0.01 indicates the nonhazardous potential of a given element [ 45 ]. In the current study, consistent with the HQ results, all HI values, except for As, were ˂0.01, corroborating that the other elements were within safe limits.…”
Section: Resultsmentioning
confidence: 99%
“…The HI values for adults and children ascended as follows: As > Cr > V > Pb > Ni > Cu > Cd > Zn ( Figure 4 A,B). An HI value of ˂0.01 indicates the nonhazardous potential of a given element [ 45 ]. In the current study, consistent with the HQ results, all HI values, except for As, were ˂0.01, corroborating that the other elements were within safe limits.…”
Section: Resultsmentioning
confidence: 99%
“…Pb has been reported to be toxic mostly to children because of their developing nervous system and pika behavior [14]. It has been reported that one of the major route of exposure to Pb is via diet [15,16]. The neurotoxic effect of Pb in children has attracted lots of attention and had continue to be a global concern especially in the developing countries; however, the mechanism of action is yet to be fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Smokeless tobacco is a major consumption of tobacco in the human population and has become the leading source of tobacco products. Heavy metals like lead, cadmium, chromium of smokeless tobacco products could induce cancer risk and need to develop industry standards and regulation for smokeless tobacco products in the manner of reducing concentrations of heavy metals [ 43 ]. The emergence of tobacco harm reduction which results in decrease the burden of smoking and smokeless tobacco-related diseases [ 44 ].…”
Section: Discussionmentioning
confidence: 99%